2021
DOI: 10.1016/j.sjbs.2021.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Vital roles of sustainable nano-fertilizers in improving plant quality and quantity-an updated review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(68 citation statements)
references
References 131 publications
0
68
0
Order By: Relevance
“…The principal mechanism for nutrient accumulation and distribution from the soil to the aerial parts of plant tissues are diffusion and bulk (mass) flow. Diffusion is the transfer of minerals along a concentration gradient from cell to cell (Marschner, 2011 ), while the bulk flow is found to be the pressure-driven distribution of solutes-water via xylem regulated by transpiration and soil nutrient availability (Lawlor et al, 2004 ; Zulfiqar et al, 2019 ; El-Saadony et al, 2021 ). The accumulation of NPs is associated with several ways of absorption/uptake via aerial surface, roots, grains, interacting atmospheric variables, rigidity of cell wall, and physiological, anatomical, and biochemical activities of the plant species/cultivars (Rajput et al, 2018a , 2021c ; Mittal et al, 2020 ).…”
Section: Role Of Nfs In Soilmentioning
confidence: 99%
See 3 more Smart Citations
“…The principal mechanism for nutrient accumulation and distribution from the soil to the aerial parts of plant tissues are diffusion and bulk (mass) flow. Diffusion is the transfer of minerals along a concentration gradient from cell to cell (Marschner, 2011 ), while the bulk flow is found to be the pressure-driven distribution of solutes-water via xylem regulated by transpiration and soil nutrient availability (Lawlor et al, 2004 ; Zulfiqar et al, 2019 ; El-Saadony et al, 2021 ). The accumulation of NPs is associated with several ways of absorption/uptake via aerial surface, roots, grains, interacting atmospheric variables, rigidity of cell wall, and physiological, anatomical, and biochemical activities of the plant species/cultivars (Rajput et al, 2018a , 2021c ; Mittal et al, 2020 ).…”
Section: Role Of Nfs In Soilmentioning
confidence: 99%
“…NPs also pass-through root hairs (symplastic and apoplastic) to the xylem to reach the stem/leaves (Mittal et al, 2020 ). The use of NFs induces a considerable rise in the physiological and biochemical indices in crop plants (Rajput et al, 2021a ) with improved chlorophyll content/SPAD units in sunflower (Pirvulescua et al, 2015 ), and also in maize, it is found to be correlated with plant productivity (Morteza et al, 2013 ; Zulfiqar et al, 2019 ; El-Saadony et al, 2021 ) associated with upgraded leaf capacity to capture sunlight, RuBisCO activity, photosynthetic CO 2 assimilation (Gao et al, 2006 ; Yang and Hong, 2006 ; Janmohammadi et al, 2016 ; Fellet et al, 2021 ), plant performance, nitrogen metabolism, and soluble proteins.…”
Section: Influence Of Nfs On Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, to produce a long-term yield, the availability of mineral nutrients is critical for improving oilseed crop output and quality [30,31]. Considering the importance of biofertilizers and NPs, this research was conducted to investigate the individual and combined effects of seed inoculation with biofertilizers (mycorrhizae and phosphorine) and the exogenous application of nanoparticles (B and Ca) on the growth metrics, seed production, yield components, and quality of peanuts grown in the sandy soil.…”
Section: Introductionmentioning
confidence: 99%